Modelling the structure of molecular clouds - I. A multiscale energy equipartition - Veltchev, Todor V.; Donkov, Sava; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2016)
Abstract. We present a model for describing the general structure of molecular clouds (MCs) at early evolutionary stages in terms of their mass-size relationsh
Advance access publication 2016 April 6
Gesehen am 04.06.2020